Effect of cutting parameters on workpiece and tool properties during drilling of Ti-6Al-4V - Celik, Yahya Hisman; Yildiz, Hakan; Ozek, Cebeli (Carl Hanser Verlag, 2016)
The main aim of machining is to provide the dimensional preciseness together with surface and geometric quality of the workpiece to be manufactured within the desired limits. Today, it is quite hard to drill widely utilized Ti-6Al-4 V alloys owing to their superior features. Therefore, in this study, the effects of temperature, chip formation, thrust forces, surface roughness, burr heights, hole diameter deviations and tool wears on the drilling of Ti-6Al-4 V were investigated under dry cutting conditions with different cutting speeds and feed rates by using tungsten carbide (WC) and high speed steel (HSS) drills. Moreover, the mathematical modeling of thrust force, surface roughness, burr height and tool wear were formed using Matlab. It was found that the feed rate, cutting speed and type of drill have a major effect on the thrust forces, surface roughness, burr heights, hole diameter deviations and tool wears. Optimum results in the Ti-6Al-4 V alloy drilling process were obtained using the WC drill.
Keywords: Drilling; forces; roughness; titanium; wear